2023
DOI: 10.1186/s12865-023-00550-7
|View full text |Cite
|
Sign up to set email alerts
|

The decreased of peripheral blood natural killer cell is associated with serum IL-2 level in the renal tubular acidosis in patients with primary sjogren’s syndrome

Abstract: Background Primary Sjogren’s Syndrome (pSS) is a lymphoproliferative disease with autoimmune characteristics, which is characterized by lymphocyte infiltration of exocrine glands and involvement and dysfunction of extraglandular organs. Renal tubular acidosis (RTA) is a common renal involvement in pSS. This study investigated the phenotypic characteristics of peripheral blood lymphocyte subsets and cytokines in pSS patients complicated with RTA (pSS-RTA). Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…6 Another study found that the absolute number of NK cells in pSS patients with renal tubular acidosis (RTA) was significantly lower than that in patients without RTA. 4 The above studies indicate that NK cells are involved in the disease development of pSS. Similarly, previous studies found that NK cells in peripheral circulation decreased in SSc, especially in patients with organ involvement, and speculated that the decrease of NK cell proportion in peripheral blood may be due to the infiltration of NK cells into the involved tissues.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…6 Another study found that the absolute number of NK cells in pSS patients with renal tubular acidosis (RTA) was significantly lower than that in patients without RTA. 4 The above studies indicate that NK cells are involved in the disease development of pSS. Similarly, previous studies found that NK cells in peripheral circulation decreased in SSc, especially in patients with organ involvement, and speculated that the decrease of NK cell proportion in peripheral blood may be due to the infiltration of NK cells into the involved tissues.…”
Section: Discussionmentioning
confidence: 85%
“…It was speculated that the reduction of NK cells in the peripheral blood of pSS patients may be due to the augmented homing of cytotoxic cells to exocrine glands, which trigger and maintain tissue inflammation by producing Th1 cytokines and cytotoxic mediators 6 . Another study found that the absolute number of NK cells in pSS patients with renal tubular acidosis (RTA) was significantly lower than that in patients without RTA 4 . The above studies indicate that NK cells are involved in the disease development of pSS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations